Comparative Analysis of Apology Strategies of English and Korean Series - putri, Sita Arum Priono; Sugiharti, Dona Rahayu (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to identify the types of apology strategies used by characters in English and Korean series using Olshtain and Cohen's (1986) theory. Additionally, this study aims to discover the differences in apology strategies between the English series